Multitasking among modern digital generations Y and Z - Barbara Gawda; Adrian Korniluk (Journal of Modern Science, 2022)
Objectives The paper aimed to examine potential differences in attention and alternating capacities between two modern digital generations, i.e., Y and Z. Although these generations are described as different, generation Z is thought ro be multitasking, there is a lack of scientific research documenting these dissimilarities.